Evaluating AI-Blockchain–IoT Capabilities and Effects on Transparency in Kenyan Seed Supply Chain - Lilian Cherotich Ronoh; Samuel Mbugua; Richard Ronoh (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Agricultural sector plays a very crucial role in Kenyan national economy and within it, is the seed sector which is it’s driver and sustainer. Despite the strides that have been made towards digitalization of the seed sector, still, there are challenges facing it, one of them being lack of transparency. This has resulted in farmers purchasing counterfeit seeds which have adverse effects on the overall crop yields and great financial losses to farmers. This study sought to evaluate the capabilities and the effects of integrating AI-Blockchain-IoT technologies to improve transparency within the seed supply chain. Data was collected from KALRO and KSC staff, farmers and agro-dealers through questionnaires and interviews and data analyses carried out were both descriptive and inferential. Findings revealed varying perceptions on the capabilities of these technologies which show that more awareness needs to be done to enlighten the stakeholders on the benefits of these technologies as well as benefits of their integration. In addition, the findings on the effects revealed that integration of AI-Blockchain-IoT technologies has a statistically significant positive effect on transparency in the seed supply chain. This study contributes to practice by providing insights into technologies that can enhance transparency so that all stakeholders can have clear visibility and access to information on the entire seed supply chain operations.
Keywords: Blockchain; IoT; AI; Transparency; Seed Supply Chain; Technology Integration